CT‐guided core biopsy of malignant lung lesions: How many needle passes are needed?. Issue 6 (1st April 2013) - Lim, Chaehun; Lee, Kyo Young; Kim, Young Kyoon; Ko, Jeong Min; Han, Dae Hee
Abstract Aim The study aims to determine the number of needle pass in the CT‐guided core needle biopsy (CNB) in making a diagnosis of pulmonary malignancy. Materials and methods A total of 434 CNB records were retrospectively reviewed. The specimen obtained from each needle pass was put in a formalin container and then labelled for separate histopathological reporting. The patients were divided into five groups according to the total number of needle passes (n = 1, n = 2, n = 3, n = 4 and n ≥ 5). In each of the groups 2–4, it was analysed how many needle passes are required before a plateau in diagnostic yield is achieved. Results CNB produced 283 true‐positive and 23 false‐negative diagnosis of malignancy. Cumulative sensitivity significantly (P < 0.05) increased between the first and second as well as the second and the third (if done) needle passes, but not between the third and fourth ones. Conclusion Three coaxial needle passes might be optimal in the diagnosis of lung malignancy.